2013
DOI: 10.5603/cj.2013.0078
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve sclerosis is a sign of increased arterial stiffness in clinically asymptomatic subjects

Abstract: p < 0.001) as an independent determinant of AVS. Conclusions: Detection of increased arterial stiffness could prevent patients from being mistakenly classified as at low or moderate risk, when they actually are at high risk. Assessment of aortic valve during echocardiography examination may offer the opportunity to identify these subjects. (Cardiol J 2013; 20, 3: 318-322)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…The results of the present study implicate that by normalizing the ET through AVR, the arterial stiffness can appropriately be captured resulting in an increased CAVI. The increased CAVI observed in AVSc patients without significantly affected hemodynamics support this hypothesis ( 5 ).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The results of the present study implicate that by normalizing the ET through AVR, the arterial stiffness can appropriately be captured resulting in an increased CAVI. The increased CAVI observed in AVSc patients without significantly affected hemodynamics support this hypothesis ( 5 ).…”
Section: Discussionmentioning
confidence: 83%
“…The pathophysiological processes in AVS share many features with atherosclerosis which is associated with arterial stiffness ( 1 ). A connection between arterial stiffness and AVS is supported by the association of aortic valve calcification and arterial stiffness ( 2 ), measured as either increased carotid femoral pulse wave velocity (cfPWV) in patients with aortic stenosis ( 3 ) or a higher cardio ankle vascular index (CAVI) ( 4 ) in patients with AVSc compared with controls ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“… 2 However, Zva cannot discriminate the valvular and arterial respective contribution, raising the notion that direct measurement of arterial stiffness would represent additional value in aortic stenosis evaluation. Indeed, increased measures of arterial stiffness have been associated with aortic valve calcium, 3 aortic valve sclerosis, 4 aortic stenosis 5 and poor prognosis after aortic valve replacement. 6 However, the effect of aortic valve replacement on arterial stiffness, although studied, remains to be clinched.…”
Section: The Importance Of Arterial Stiffness In Aortic Valve Stenosismentioning
confidence: 99%
“…Four studies [16,18,25,31] showed a significantly higher PWV in the 230 AVSc patients as without heterogeneity among studies (I 2 = 25.9%; p = 0.249). Of interest, after excluding the study by Erdogan et al [16], that enrolled non aged-matched cohorts, the lack of difference in AIx values between AVSc patients and controls was consistently confirmed (MD: 0.99 mm; 95%CI: -1.07, 3.06; p = 0.347, I 2 = 41,5%; p = 0.162).…”
Section: Pulse Wave Velocity (Pwv)mentioning
confidence: 99%